College students still maintain the traditional Chinese concept of love - Juan Sun; Fengqing Li; Shiqi Wang; Zeyu Lu; Chengyi Zhang (Heliyon, 2023)
A cross-sectional census was conducted on all students at the campus of Inner Mongolia Medical University using a self-administered questionnaire. This study aimed to investigate their love from psychological pressure, behavioral characteristics, social cognition, etc. Our results show that all students cultivate feelings and become lifelong partners as their motivation for love. Among the population with various demographic characteristics, the prevalence of love among disadvantaged groups is low; that is, women are lower than men, and those from rural are lower than those from cities. After balancing areas and gender, mental working families have a high prevalence of love. Instead, students whose parents' high expectations pressure their children to have a high love prevalence. This is due to China's specific historical perspective. Our results suggested that although China has been deeply integrated with the world and has more frequent ideological and cultural exchanges, college students still inherit China's traditional outlook on love.